Validitas Multimedia Interaktif Lectora Inspire pada Submateri Pemanfaatan Keanekaragaman Hayati Berbasis Tumbuhan Kerajinan - Anggie Febiola; Syamswisna Syamswisna; Andi Besse Tenriawaru (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
In assessing the availability of the local potentials, learning biology has a vital role. By the support of interactive multimedia, the delivery of materials and a sense of caring for the environment can be built by students easily. This research aims to find out the feasibility of interactive multimedia lectora inspire as a learning media in biodiversity sub-material. Research methods use quantitative descriptive and data analysis using RTVTK calculations. Lectora inspire validation is conducted by three material experts with three aspects and 11 assessment criteria and three media experts with six aspects and 13 assessment criteria. Validation results get an average of total validation (RTVTK) material experts of 3.89 and media experts of 3.65. The interactive multimedia Lectora inspires the sub-material of the use of biodiversity for class X HIgh School is considered appropriate to be used as learning media.